Prevalence and risk factors of HSV-2 infection and HSV-2/HIV coinfection in men who have sex with men in China: a multisite cross-sectional study - Yin, Yue-Ping; Chen, Shao-Chun; Wang, Hong-Chun; Wei, Wan-Hui; Wang, Qian-Qiu; Liang, Guo-Jun; Jiang, Ning; Han, Yan; Chen, Xiang-Sheng; Wang, Baoxi (Sexually transmitted diseases, 2012)
To determine the prevalence and risk factors of herpes simplex virus type 2 (HSV-2) infection and its coinfection with human immunodeficiency virus (HIV) in men who have sex with men (MSM) in China. A convenience sample of 1462 MSM were recruited from different settings (an STD clinic, a health center, and MSM venues) in 3 cities in China. Blood specimens were collected for testing for antibodies to HSV-2 and HIV to determinate the seroprevalence of HSV-2 infection and HSV-2/HIV coinfection. Information on sociodemographic and behavioral characteristics was collected to determine the risk factors associated with the infections. The prevalence of HSV-2 infection in 1462 MSM was 16.0% (95% confidence interval [CI], 14.2%-18.0%), the prevalence of HIV infection in this population was 9.5% (95% CI, 8.1%-11.1%), and the rate of coinfection of HSV-2 and HIV was 3.2% (95% CI, 2.4%-4.3%). Multivariate logistic regression analysis showed that risk factors for HSV-2 infection included age older than 30 years, education level lower than senior high school, involvement in commercial sex work, and HIV-positive status. Education level lower than junior high school and history of sexual abuse were associated with HSV-2/HIV coinfection. The high prevalence of HSV-2 infection and HSV-2/HIV coinfection among MSM in China suggests that an increased focus on HSV control is warranted within China's prevention and intervention programs targeted toward MSM.